Torma Code Interactive Media: A Problem Based Learning Innovation to Enhance Critical Thingking Skills among Elementary School Students - Ainiyyah, Qurrotul; Siswanto, Joko; Sulianto, Joko (FKIP - Universitas Riau, 2025)
The rapid development of learning technology requires teachers to use innovative media that encourage students’ higher-order thinking skills. In elementary schools, science learning is still dominated by textbooks and teacher explanations, resulting in low student engagement and limited opportunities for developing critical thinking skills. Therefore, interactive media that supports inquiry and exploration is needed. This study aims to develop and evaluate the effectiveness of Torma Code, an interactive learning media based on the Problem Based Learning (PBL) model, in the Natural and Social Sciences (IPAS) subject on the topic of the sense of sight to enhance students’ critical thinking skills. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The media, teaching module, and test instruments were validated by two experts and categorized as very valid with average feasibility scores exceeding 90%. Practicality testing involving teachers and students also resulted in a very practical category with scores above 92%. Effectiveness testing through a paired sample t-test showed a significant difference between pretest and posttest (Sig. < 0.05), while an N-Gain score of 0.55 indicated moderate improvement. Thus, Torma Code is valid, practical, and effective in improving critical thinking skills.